Laryngeal paralysis secondary to cervical bite injuries in five dogs. Issue 2 (4th March 2022) - Picavet, PP; Hamon, M; Etienne, A-L; Guieu, L-V; Claeys, S; Billen, F; Noël, S
ABSTRACT: Case histories: Medical records of a veterinary hospital in Belgium were reviewed for dogs (n = 5) that presented between 2016 and 2019 with laryngeal paralysis secondary to bite wounds to the cervical region received while fighting with other dogs. The time elapsed between the trauma and presentation was from a few hours up to 5 days. Clinical findings and treatment: Bilateral laryngeal paralysis was identified in three dogs and unilateral laryngeal paralysis in two dogs via endoscopic assessment of laryngeal function. The primary concomitant lesions included tracheal injury in 3/5 dogs and oesophageal injury in 1/5 dogs. One dog with bilateral laryngeal paralysis was treated medically as no signs of dyspnoea were present. Surgical management was elected in 4/5 dogs based on evaluation of their clinical status and lesions revealed by endoscopic examination of upper gastrointestinal and respiratory tracts. Dogs underwent surgical procedures that were determined to be appropriate for treatment of the lesions identified on clinical examination, diagnostic imaging, and endoscopy. The cervical region was explored through a ventral midline approach in 2/4 cases, to close tracheal perforations. Temporary tracheostomy was performed in 2/4 cases. Procedures to correct brachycephalic airway obstructive syndrome were performed in 2/4 cases. Cricoarytenoid lateralisation was performed in 2/4 dogs. Dogs were hospitalised for 2–10 days and received antimicrobial therapy before surgery and for 2–3 weeks after surgery. Physical examination and respiratory function were normal in 3/5 dogs 4–6 months after discharge. Information regarding outcomes for two cases was obtained from the owners by telephone assessment 1–6 months after surgery. The owner of each dog reported the respiratory function to be excellent. Diagnosis: Uni- or bilateral, transient or permanent laryngeal paralysis with concomitant oesophageal, tracheal, or laryngeal lesions following cervical dog bite injuries diagnosed by endoscopic examination of upper gastrointestinal and respiratory tracts. Clinical relevance: This case series describes the diagnosis and management of dogs with laryngeal paralysis secondary to cervical dog bite injuries. To the authors' knowledge, this is the first published report documenting bilateral laryngeal paralysis secondary to cervical dog bite injuries. Clinicians should be aware of this pathology and the importance of investigating laryngeal function in dogs presenting with cervical bites, particularly those with inspiratory dyspnoea. Upper airway and digestive endoscopy are recommended for complete assessment of cervical traumatic injuries.